The Role of Oxymatrine in Amelioration of Acute Lung Injury Subjected to Myocardial I/R by Inhibiting Endoplasmic Reticulum Stress in Diabetic Rats. (26th November 2020) - Huang, Yongpan; Long, Xian; Li, Xinliang; Li, Saihua; He, Jianbin
Abstract : Background . Oxymatrine (OMT) is the primary pharmacological component of Sophora flavescens Aiton., which has been shown to possess potent antifibrotic, antioxidant, and anti-inflammatory activities. The aim of the present study was to clarify the protective mechanism of OMT on acute lung injury (ALI) subjected to myocardial ischemia/reperfusion (I/R). Methods . A myocardial I/R-induced ALI model was achieved in diabetic rats by occluding the left anterior descending coronary artery for 1 h, followed by reperfusion for 1 h. The levels of inflammatory factors (tumor necrosis factor- α, interleukin- (IL-) 6, and IL-17) in bronchoalveolar lavage fluid were assessed using commercially available kits. The index of myocardial injury, including the detection of cardiac troponin I (cTnI), cardiac troponin T (cTnT), lactate dehydrogenase (LDH), and creatine kinase-MB (CK-MB), was also determined using commercially available kits. Hematoxylin and eosin staining and terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling were used to identify histological changes. The expression levels of endoplasmic reticulum chaperone BiP (GRP78), DNA damage-inducible transcript 3 protein (CHOP), eukaryotic translation initiation factor 2-alpha kinase 3 (PERK), inositol dependent enzyme 1 α (IRE1 α ), ATF6, caspase-3, -9, and-12, Bcl-2, and Bax were determined by Western blotting. The mRNA expression levels of GRP78 and CHOP were detected by reverse transcription-quantitative PCR. Results . Myocardial I/R increased the levels of cTnI, cTnT, LDH, and CK-MB in diabetic rats. Damaged and irregularly arranged myocardial cells were also observed, as well as more serious ALI with higher lung injury scores and WET/DRY ratios and lower PaO2 . Moreover, the expression of key proteins of endoplasmic reticulum stress (ERS) was increased by I/R injury, including phosphorylated- (p-) PERK, p-IRE1ɑ, and ATF6, as well as decreased levels of apoptosis. These effects were all significantly reversed by OMT treatment. Conclusions . OMT protects against ALI subjected to myocardial I/R by inhibiting ERS in diabetic rats.